Rationale for Crime and Cybercrime Perpetuators in Edo State Nigeria - Obasi, Rosemary Obiageli; Osemwegie-Ero, Joy Omeghie; Erhirhie, Felix Erhinyoja; Jackson-Akhigbe, Beauty E.; Atarere, Lovy Omotie-Ivie; Ikponmwoba, Osasenaga Gift (Archives of Business Research, 2024)
The paper examined the rationale for crime and cybercrime perpetuators in Edo state, Nigeria. The population of the study comprised of six (06) correctional centers in Edo State. But, was limited to inmates convicted of cybercrime in the Oko correctional center, Benin City. As a result of the prison break that occurred in August 2020. The simple random sampling techniques and the Taro Yamane formular was used to derive the sample size of 148 respondents. Primary data was sourced and used. While, the two-way factor anova analytical tool was used for the analysis. Findings of the study revealed among others that, opportunity has a positive and significant relationship with cybercrime in Edo state. Incentives has a positive and significant relationship with cybercrime in Edo state and rationalization has a positive and significant relationship with cybercrime in Edo state. The study concluded that cybercrime is an activity that can be detrimental to the financial activities of an organization and the society at large. Based on the results, the study recommends that the avenue that has been created as a result of loopholes embedded in the different dynamics of the legal society should be properly investigated and blocked by the relevant regulatory and prosecuting bodies in order to reduce the occurrence of cybercrime. The Government should make the society enabling for investors, which could provide jobs for thousand other individuals, which could reduce the number of youths and individuals that are lured into cybercrime as a result of the incentives and benefits it brings. Lastly, there should be frequent awareness and lectures by regulatory and security agencies on the dangers of cybercrime effect on business organizations and the society at large.